A STUDY ON THE LEARNING BELIEFS OF CHINESE AS A SECOND FOREIGN LANGUAGE FOR ENGLISH MAJORED STUDENTS OF BANKING UNIVERSITY HO CHI MINH CITY - Vu, Luu Hon (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4614, 2020)
The research surveyed the learning beliefs of Chinese as a second foreign language for English majored students of Banking University Ho Chi Minh city. Based on the theory of beliefs in foreign language learning by Horwitz (1985), we conducted a questionnaire survey with 177 students. The questionnaire results indicate that: firstly, Chinese is relatively easy to learn; secondly, children have better language learning capacity than adults; third, focus on phonetics, vocabulary and culture, not grammar; fourth, learning Chinese is useful for yourself. Female students focus on phonetics more than male students. Second-year students focus on phonetics more than third-year students, but not more grammar like third-year students. Unlike students from the central region, students from the northern and southern regions said that they must come to China to learn Chinese. The belief that "Chinese language is easy to learn", the confident and proactive attitude of using Chinese language has a positive impact on students' learning results.